2015
DOI: 10.1088/0960-1317/25/9/095018
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and analysis of awl-shaped serpentine microsprings for large out-of-plane displacement

Abstract: This work investigates a novel awl-shaped serpentine microspring for a suspension structure, with a lower spring constant under the same unit layout area in out-of-plane motion. Using Castigliano's theorem, the spring constant of the microspring was theoretically derived and simulations were performed using COMSOL Multiphysics to verify the theoretical results. The proposed awl-shaped serpentine microspring was successfully fabricated using siliconbased micromachining. Experiments were conducted to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…This type of arrangement is a well-defined mechanical suspension system. By applying Castigliano's theorem to each beam element in the springs [15], the displacement of the center square plate in the spring system can be related to the total force and torque applied to the springs. Considering the mechanism of airflow sensing of the fin sensor, vertical translation of the center square plate becomes negligible compared to rotation, since the load from vertical direction is very low.…”
Section: B Modeling and Design Optimizationmentioning
confidence: 99%
“…This type of arrangement is a well-defined mechanical suspension system. By applying Castigliano's theorem to each beam element in the springs [15], the displacement of the center square plate in the spring system can be related to the total force and torque applied to the springs. Considering the mechanism of airflow sensing of the fin sensor, vertical translation of the center square plate becomes negligible compared to rotation, since the load from vertical direction is very low.…”
Section: B Modeling and Design Optimizationmentioning
confidence: 99%
“…The mechanical spring is a key element in various micro-electro-mechanical systems (MEMS) devices such as micro-actuators, inertial switches, accelerometers, and so on [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In these devices, mechanical springs are designed for single or multi-axis motion.…”
Section: Introductionmentioning
confidence: 99%
“…In these devices, mechanical springs are designed for single or multi-axis motion. Up to date, there are many types of springs introduced for applications in controlling in-plane motions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The springs can be designed for compliance to the linear movements in 𝑥 and 𝑦 axes [1-4, 7, 9, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Sharma and Gupta [32] designed a nonuniform serpentine spring for radio frequency MEMS switches; this design reduced actuating voltage. Chou, Lin, and Chen designed and analyzed the mechanical properties of awl-shaped serpentine microsprings (ASSMs) for in-plane and out-of-plane motion [33,34]. They found that under the same total effective lengths and folds, for the out-of-plane motion, the ASSMs had a smaller spring constant to layout area ratio than the traditional serpentine microsprings.…”
Section: Introductionmentioning
confidence: 99%